2020
DOI: 10.3389/fpls.2020.533046
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Hormones Inhibit Differentiation of Young Ears in Maize (Zea mays L.) Under Heat Stress

Abstract: Global warming frequently leads to extreme temperatures, which pose a serious threat to the growth, development, and yield formation of crops such as maize. This study aimed to deeply explore the molecular mechanisms of young ear development under heat stress. We selected the heat-tolerant maize variety Zhengdan 958 (T) and heatsensitive maize variety Xianyu 335 (S), and subjected them to heat stress in the V9 (9th leaf), V12 (12th leaf), and VT (tasseling) growth stages. We combined analysis of the maize phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“…This study used the heat-sensitive "Xianyu 335" (XY335)and heat-insensitive maize varietiy: "Zhengdan 958" (ZD958) (Wang et al, 2020a). Both are common maize varieties in China.…”
Section: Experimental Design and Field Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used the heat-sensitive "Xianyu 335" (XY335)and heat-insensitive maize varietiy: "Zhengdan 958" (ZD958) (Wang et al, 2020a). Both are common maize varieties in China.…”
Section: Experimental Design and Field Managementmentioning
confidence: 99%
“…The rising levels of carbon dioxide in the atmosphere causes a greenhouse effect that results in increased temperatures and climatic changes (Xuan et al, 2020). Rising temperature is a global issue because of its impact on crop growth and yield (Wang et al, 2020a). Maize is more sensitive to heat stress (one of the most important abiotic stresses) than wheat and rice (Zhao et al, 2017;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many candidate genes were associated with coleoptile length/root length ratio under well-watered conditions. In Li et al [ 69 ], the gene Zm00001d034129 ( Peroxidase 73 ) was associated with maize seedling leaves under cold and heat stress. The authors reported that common genes for both treatments were enriched in the hydrogen peroxidase metabolic process, which is the case of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…This gene belongs to the ERF family, genes of which are important regulators involved in cold and heat stresses. This gene was up-regulated under cold and heat conditions in Li et al [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation